1985
DOI: 10.1088/0026-1394/21/2/001
|View full text |Cite
|
Sign up to set email alerts
|

The Triple Point of Xenon as a Possible Defining Point on an International Temperature Scale

Abstract: The use of an additional defining point on the International Temperature Scale between 90.188 K and 273.15 K is advocated. The triple point of xenon is suggested as the candidate and an experimental technique which gives the required degree of reproducibility for the melting curves is described. Results obtained for natural xenon and xenon enriched to 80% 136Xe are given. It is concluded that the triple point of xenon can be realized with sufficient reproducibility that it can be used as a defining point on an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…18 Our adsorption isotherm measurements span seven temperatures in the range between 95 and 160 K. All of the temperatures in this interval are below xenon's triple point (T t = 161.389 K), so solid xenon is the phase that condenses at saturation in our measurements. 28 In all cases, the measurements were started from a freshly re-evacuated sample (i.e., from zero loading) and were continued, without re-evacuation, until the equilibrium pressure reached saturation.…”
Section: Resultsmentioning
confidence: 99%
“…18 Our adsorption isotherm measurements span seven temperatures in the range between 95 and 160 K. All of the temperatures in this interval are below xenon's triple point (T t = 161.389 K), so solid xenon is the phase that condenses at saturation in our measurements. 28 In all cases, the measurements were started from a freshly re-evacuated sample (i.e., from zero loading) and were continued, without re-evacuation, until the equilibrium pressure reached saturation.…”
Section: Resultsmentioning
confidence: 99%
“…K ) with its triple point does not appreciably change the non-uniqueness. point is not sufficiently reproducible to be used for this purpose because of difficulties in obtaining gas of high purity and reproducible isotopic composition [17]. Consequently, the mercury triple point (234.3 156 K) was chosen as the best compromise, being more reproducible than the triple point of xenon, but less suitably located.…”
Section: Temperatures Fvom 138 K To 27316 Kmentioning
confidence: 99%
“…The triple point of xenon has long been recognized [1] as a potentially useful calibration point for the International Temperature Scale (ITS). As work progressed towards the revision of the ITS during the late 1980s, the triple point of xenon was proposed [2][3][4] as a defining fixed point of the ITS-90 [5] due to its desirable placement (160.405 K [6]) nearly halfway between the triple point of argon (83.8058 K) and the triple point of water (TPW) (273. 16 K).…”
Section: Introductionmentioning
confidence: 99%
“…Reports of the thermal behaviour of xenon invariably indicated that the broad melting range and the extent of the variation in liquidus points (liquid fraction equal to 1) among different samples precluded its adoption as a defining point [2,[7][8][9][10][11][12][13][14]. There was speculation but no conclusion as to whether this variability was due to impurity content or isotopic composition.…”
Section: Introductionmentioning
confidence: 99%